Digital Catechesis as Cyber-Theological Practice: Model Integration, Semiotic Capacity, and Hybrid Faith Formation in Post-Pandemic Indonesia - Agustinus Manfred Habur (Khazanah Theologia, 2025)
The COVID-19 pandemic precipitated unprecedented digital transformation across religious institutions, with approximately 80% of congregations worldwide adopting digital ministry by mid-2020. However, existing research predominantly examines isolated catechetical models, neglects semiotic dimensions, inadequately analyzes pedagogical mechanisms across platforms, and overlooks context-specific implementation in infrastructure-diverse settings, particularly in the Global South where 60% of Catholics reside. This study examined how the Diocese of Ruteng, Indonesia's largest Catholic diocese, implemented digital catechesis during 2020–2022, focusing on model integration, language strategies, pedagogical approaches, and contextual adaptation across heterogeneous infrastructural contexts. A qualitative phenomenological design involved 39 participants (diocesan leaders, priests, catechists, and young Catholics) selected through purposive maximum variation sampling across urban, sub-district, and rural parishes. Data collection combined structured interviews, platform observations of 150+ posts, and document analysis. Thematic analysis generated three major themes with methodological triangulation ensuring rigor. Findings revealed simultaneous deployment of three complementary catechetical models creating comprehensive ecosystems. Persistent misalignment existed between content production (55–75% conceptual language) and youth preferences (symbolic language generating substantially higher interaction), attributed to semiotic capacity gaps rather than awareness deficits. Pedagogical effectiveness proved fundamentally constrained by facilitator capacity rather than platform affordances, with asynchronous platforms remaining underutilized despite dialogic potential. Rural parishes developed innovative "digitally-sourced analog catechesis" downloading content for offline face-to-face sessions demonstrating that digital transformation in resource-constrained contexts requires reconceptualizing digital-analog boundaries. Successful digital catechesis demands integrated model strategies, semiotic capacity building, facilitator training for asynchronous pedagogy, access equity attention, and institutional support for hybrid approaches. Effectiveness depends on context-responsive adaptation rather than uniform solutions. Contribution: This research introduces "digitally-sourced analog catechesis" as a fourth model in digital catechesis typology and establishes "semiotic capacity" as a critical variable in content effectiveness, challenging technological determinism while providing evidence-based frameworks for religious education in infrastructure-diverse contexts, with implications for faith formation practices globally.